“Crowdfunding in Emerging Markets: Prospects in India” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Start-up firms these days are always seeking a means of acquiring funding to achieve their objectives and foster the growth of their enterprises. Over the last decade, new approaches to acquiring capital have emerged in the business sector. One option is crowdsourcing. Crowdfunding has rapidly become a popular method of financing in a short time. Crowdfunding is a concept that has significant importance. It contributes to the rapid growth of a new and emerging business, while also providing new investment opportunities and diversifying the portfolios of investors. Startups with unique and inventive ideas may be able to secure funding by advertising their concepts on social media platforms. These social media platforms facilitate the connection between entrepreneurs and those who support the cause or have a potential interest in creative concepts. Crowdfunding is still in its nascent stage of development in India. This study examines the use of crowdfunding in India as an alternative means of obtaining company capital compared to stock shares and other financial sources. The objective of this research has been to the challenges and complexities it entails, and its emphasis on Indian circumstances. The study focused on analysing the various forms of crowdfunding and the regulatory framework governing crowdfunding in India. The study asserts that crowdfunding initiatives have significant potential inside the Indian venture capitalist sector, provided that the uncertainty surrounding its laws and regulations is resolved. This concept was first used in the year 2000 and had been rapidly gaining popularity worldwide